Correlation and path coefficient analysis for seed yield and its component traits in castor (Ricinus communis L.): Correlation and path coefficient analysis for seed yield and its component traits in castor (Ricinus communis L.) - S K MOHANTY; P N JAGADEV; C LAVANYA; C M KHANDA (Journal of Oilseeds Research, 2020)
A field experiment was conducted during kharif 2018 with 15 genotypes of castor at AICRP on Castor, RRTTS, Bhawanipatna, Odisha to study the relationship between castor seed yield and its nine component traits. Four characters showed significant positive correlation with seed yield/plant at both genotypic and phenotypic level while four characters had higher positive direct effect on seed yield. Three characters viz., number of capsules/primary spike, number of effective spikes/plant and oil content (%) with high positive correlations with seed yield/plant and positive direct effect on seed yield, can be used as selection criteria in breeding for higher seed yield in castor.